Isotherms and Kinetic Studies of Copper Removal from Textile Wastewater and Aqueous Solution Using Powdered Banana Peel Waste as an Adsorbent in Batch Adsorption Systems - Momina Seleman; Takele Sime; Abate Ayele; Assefa Sergawie; Thabo Nkambule; Jemal Fito (International Journal of Biomaterials)
Heavy metals that are present in surface water and wastewater are becoming a severe environmental problem. Because of its toxicity, heavy metal removal has become the main priority for environmental concerns. Banana peels are low-cost agricultural waste that could be used for heavy metal adsorption in wastewater. The main objective of this study is to evaluate the effective powdered banana peel for the removal of copper (II) from aqueous solutions and real wastewater. The banana peels were collected from domestic waste and ground to get a particle size of 150 µm. Powdered banana peel waste adsorbent (PBPWA) contained moisture content, ash content, volatile matter, and bulk density of 3.8%, 3.5%, 37.5%, and 0.02 g/cm3, respectively. The Fourier-transform infrared spectroscopy (FTIR) results showed that the alkyne, aldehyde, and amide functional groups were dominant in the powdered banana peel surface, and the scanning electron microscope showed the morphology of the adsorbent. Physicochemical characteristics of the raw wastewater revealed that the concentration of Cu (II), Pb (II), COD, BOD5, and Cd (II) were 2.75 mg/L, 2.02 mg/L, 612.16 mg/L, 185.35 mg/L, and 0.01 mg/L, respectively. At pH 5, adsorbent dose of 2g/100 mL, initial copper (II) concentration of 80 mg/L, and contact time of 90 min, the maximum removal efficiency of synthetic wastewater was 96.8% and textile wastewater was 69.0%. The adsorption isotherm fitted well with the Langmuir isotherm model at R2 = 0.99. The kinetics of copper (II) adsorption followed the second-order kinetic model better. Finally, these studies showed that banana peel bio-adsorbent is a potential adsorbent for heavy metal removal from synthetic and textile wastewater.